Efficient and sustained FOXP3 locus editing in hematopoietic stem cells as a therapeutic approach for IPEX syndrome - Swati Singh; Cole M. Pugliano; Yuchi Honaker; Aidan Laird; M. Quinn DeGottardi; Ezra Lopez; Stefan Lachkar; Claire Stoffers; Karen Sommer; Iram F. Khan; David J. Rawlings (Molecular Therapy: Methods & Clinical Development, 2024)
Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a monogenic disorder caused by mutations in the FOXP3 gene, required for generation of regulatory T (Treg) cells. Loss of Treg cells leads to immune dysregulation characterized by multi-organ autoimmunity and early mortality. Hematopoietic stem cell (HSC) transplantation can be curative, but success is limited by autoimmune complications, donor availability and/or graft-vs.-host disease. Correction of FOXP3 in autologous HSC utilizing a homology-directed repair (HDR)-based platform may provide a safer alternative therapy. Here, we demonstrate efficient editing of FOXP3 utilizing co-delivery of Cas9 ribonucleoprotein complexes and adeno-associated viral vectors to achieve HDR rates of >40% in vitro using mobilized CD34+ cells from multiple donors. Using this approach to deliver either a GFP or a FOXP3 cDNA donor cassette, we demonstrate sustained bone marrow engraftment of approximately 10% of HDR-edited cells in immune-deficient recipient mice at 16 weeks post-transplant. Further, we show targeted integration of FOXP3 cDNA in CD34+ cells from an IPEX patient and expression of the introduced FOXP3 transcript in gene-edited primary T cells from both healthy individuals and IPEX patients. Our combined findings suggest that refinement of this approach is likely to provide future clinical benefit in IPEX.